2016
DOI: 10.7554/elife.12556
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii peptide ligands open the gate of the HLA class I binding groove

Abstract: HLA class I presentation of pathogen-derived peptide ligands is essential for CD8+ T-cell recognition of Toxoplasma gondii infected cells. Currently, little data exist pertaining to peptides that are presented after T. gondii infection. Herein we purify HLA-A*02:01 complexes from T. gondii infected cells and characterize the peptide ligands using LCMS. We identify 195 T. gondii encoded ligands originating from both secreted and cytoplasmic proteins. Surprisingly, T. gondii ligands are significantly longer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 50 publications
3
93
0
Order By: Relevance
“…Other types of influences of peptide length on binding motifs have been previously reported, such as N-or C-terminal extensions (16,36). Most alleles analyzed in this work (except those shown in Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other types of influences of peptide length on binding motifs have been previously reported, such as N-or C-terminal extensions (16,36). Most alleles analyzed in this work (except those shown in Fig.…”
Section: Discussionmentioning
confidence: 90%
“…For this reason, existing HLA class I ligand prediction tools tend to focus on 9 and 10 mers, and only recently have peptides of different lengths been incorporated in training sets (8,35). This is in stark contrast with HLA peptidomics data in which many longer peptides are routinely identified (15,16,21,36). In this study, we take advantage of this unique property to explore how binding motifs change as a function of peptide length.…”
Section: Influence Of Peptide Length On Binding Motifsmentioning
confidence: 80%
“…To explore further the molecular determinants of peptide binding to CD1d, we modified the p99 peptide at the anchor residue Trp 7 by mutating the residue to Lys and covalently attaching to it a palmitate moiety. The lipopeptide generated (p99p) was crystallized in complex with CD1d at a resolution of 1.8 Å. p99p binds in a similar orientation and conformation to p99, adopting an ␣-helical conformation and sitting above the antigen binding groove (Fig.…”
Section: Structure Of Lipopeptide Bound To Cd1d Suggests Novel Peptidmentioning
confidence: 99%
“…MHC class II peptides are also bound in an extended conformation but, because of the open nature of the groove, tend to be longer (14 -20 residues) (1). Binding of longer peptides has also been reported for MHC class I, and in those cases, the peptides either bulged out of the groove (2)(3)(4)(5), bound in a zig-zag fashion (6), or induced the opening of the F pocket to protrude with their C termini into the solvent (7). In both MHC class I and II, peptides are bound with specific anchor residues inside allele-specific pockets (denominated A to F), thereby exposing alternating amino acids for T cell receptor recognition (5,6).…”
mentioning
confidence: 99%
“…KIR genes are also associated with many other infectious diseases171819. Additionally, both murine and human studies have shown that major histocompatibility complex (MHC) class I (called HLA class I in human) are associated with Toxoplasma susceptibility20212223242526.…”
mentioning
confidence: 99%